The Magdalen girls - Alexander, V. S. (Kensington Books, 2017)
When her beauty provokes a lustful revelation from a young priest, sixteen-year-old Teagan is sent to one of Dublin's Magdalen Laundries for fallen women, where she befriends two other girls who help her endure the harsh captivity.